Unsuspected Involvement of Spinal Cord in Alzheimer Disease - Lorenzi, Roberta Maria; Palesi, Fulvia; Castellazzi, Gloria; Vitali, Paolo; Anzalone, Nicoletta; Bernini, Sara; Cotta Ramusino, Matteo; Sinforiani, Elena; Micieli, Giuseppe; Costa, Alfredo; D’Angelo, Egidio; Gandini Wheeler-Kingshott, Claudia A. M. (Frontiers in Cellular Neuroscience, 2020)
Objective: Brain atrophy is an established biomarker for dementia, yet spinal cord involvement has not been investigated to date. As the spinal cord is relaying sensorimotor control signals from the cortex to the peripheral nervous system and viceversa, it is an interesting question to assess whether it is affected by atrophy in a disease that is known for its involvement of cognitive domains first and foremost, with motor symptoms being clinically assessed too. We hypothesize that Alzheimer’s Disease severe atrophy can affect the spinal cord and that spinal cord atrophy is an important in-vivo imaging biomarker contributing to understanding neurodegeneration associated with dementia. Methods: 3DT1 images of 31 Alzheimer’s disease(AD) and 35 healthy-control(HC) subjects were processed to calculate volumes of brain structures and cross-sectional area(CSA) and volume(CSV) of the cervical cord(per vertebra and C2-C3 pair(CSA23, CSV23)).Correlated features(ρ>0.7) were removed, and best subset identified for patients’ classification with Random Forest algorithm. General linear model regression was used to find significant differences between groups(p<=0.05). Linear regression was implemented to assess the explained variance of the Mini Mental State Examination(MMSE) score as dependent variable with best features as predictors. Results: Spinal cord features were significantly reduced in AD, independently of brain volumes. Patients classification reached 76%accuracy when including CSA23 together with volumes of hippocampi, left amygdala, white and grey matter, with 74%sensitivity and 78%specificity. CSA23 alone explained 13%of MMSE variance. Discussion: Our findings reveal that C2-C3 spinal cord atrophy contributes to discriminate AD from HC, together with established features. Results show that CSA23, calculated form the same 3DT1 as all other brain volumes(including right and left hippocampi), has a considerable weight in classification tasks warranting further investigations. Together with recent studies revealing that AD atrophy is spread beyond the temporal lobes, our result adds the spinal cord to a number of unsuspected regions involved in the disease. Spinal cord atrophy explains also cognitive scores, which could significantly impact how we model sensorimotor control in degenerative diseases with a primary cognitive domain involvement. Prospective studies should be purposely designed to understand the mechanisms of atrophy and the role of the spinal cord in AD.